Autism Spectrum Social Stories In Schools Trial (ASSSIST): study protocol for a feasibility randomised controlled trial analysing clinical and cost-effectiveness of Social Stories in mainstream schools. Issue 7 (9th July 2014) - Wright, Barry; Marshall, David; Collingridge Moore, Danielle; Ainsworth, Hannah; Hackney, Lisa; Adamson, Joy; Ali, Shehzad; Allgar, Victoria; Cook, Liz; Dyson, Lisa; Littlewood, Elizabeth; Hargate, Rebecca; et al.
Abstract : Introduction: Current evidence suggests that Social Stories can be effective in tackling problem behaviours exhibited by children with autism spectrum disorder. Exploring the meaning of behaviour from a child's perspective allows stories to provide social information that is tailored to their needs. Case reports in children with autism have suggested that these stories can lead to a number of benefits including improvements in social interactions and choice making in educational settings. Methods and analysis: The feasibility of clinical and cost-effectiveness of a Social Stories toolkit will be assessed using a randomised control framework. Participants (n=50) will be randomised to either the Social Stories intervention or a comparator group where they will be read standard stories for an equivalent amount of time. Statistics will be calculated for recruitment rates, follow-up rates and attrition. Economic analysis will determine appropriate measures of generic health and resource use categories for cost-effectiveness analysis. Qualitative analysis will ascertain information on perceptions about the feasibility and acceptability of the intervention. Ethics and dissemination: National Health Service Ethics Approval (NHS; ref 11/YH/0340) for the trial protocol has been obtained along with NHS Research and Development permission from Leeds and York Partnership NHS Foundation Trust. All adverse events will be closely monitored, documented and reported to the study Data Monitoring Ethics Committee. At least one article in a peer reviewed journal will be published and research findings presented at relevant conferences. Trial registration number: ISRCTN96286707.